Cost Effectiveness Analysis: Small Country Pediatric Cardiac Surgery Program Development - Cardarelli, Marcelo; Chadikovski, Vladimir; Novick, William (Journal of Humanitarian Cardiovascular Medicine, 2022)
Abstract Background The cost-effectiveness of sending children abroad for treatment of their congenital heart disease (CHD) in small population countries versus developing a local program should be carefully considered. We investigated the cost-effectiveness analysis of developing such program in a small Eastern-European country. Methods Calculated costs during different stages in the development of a program in North Macedonia were obtained from the Ministry of Health. All patients diagnosed and surgically treated between 2010 and 2017 were included along 3 distinctive periods. 2010-2012 - Outsourcing (All patients sent abroad for surgical treatment) 2013-2016 - Foundational (Program development with assistance from a global charity organization) 2017 - Tutelage Period (Semi-Independent program) Cost-Effectiveness is provided in US per Disability Adjusted Life Years (DALY) as unit of health value. Results Between January 2010 and December 2017, a total of 384 patients diagnosed with CHD underwent surgical treatment at government expense. The breakdown was: 125; 204 and 55 patients in each period.The cost-effectiveness of the intervention was 315; 297 and 251 per DALY averted respectively. Conclusions Surgical treatment of patients born with CHD is a highly cost-effective intervention irrespective of the approach taken. Even after accounting for the initial capital investment costs, the development of a local pediatric cardiac surgery program seems to be slightly more cost-effective than outsourcing.